2015
DOI: 10.1515/msp-2015-0084
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and structural properties of titanium dioxide deposited by innovative magnetron sputtering process

Abstract: Titanium dioxide thin films were prepared using two types of magnetron sputtering processes: conventional and with modulated plasma. The films were deposited on SiO 2 and Si substrates. X-ray diffraction measurements of prepared coatings revealed that the films prepared using both methods were nanocrystalline. However, the coatings deposited using conventional magnetron sputtering had anatase structure, while application of sputtering with modulated plasma made possible to obtain films with rutile phase. Inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…It was indicated that amorphous TiO 2 nanotubes are softer than mixture of amorphous and crystallized TiO 2 (anatase) nanotubes. Also, the geometry of nanotubes, i.e., their length and wall thickness will affect the hardness measurement result [46,47,48]. In addition, it is well-known that the radius of the nanoindenter’s tip rounding has an effect on the test results.…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that amorphous TiO 2 nanotubes are softer than mixture of amorphous and crystallized TiO 2 (anatase) nanotubes. Also, the geometry of nanotubes, i.e., their length and wall thickness will affect the hardness measurement result [46,47,48]. In addition, it is well-known that the radius of the nanoindenter’s tip rounding has an effect on the test results.…”
Section: Discussionmentioning
confidence: 99%
“…Also the geometry of nanotubes, i.e. their length and wall thickness will affect the hardness measurement result [48][49][50]. In addition, it is well-known that the radius of the nanoindenter's tip rounding has an effect on the test results.…”
Section: Discussionmentioning
confidence: 99%
“…It is a hard, corrosion resistant, and well biocompatible material with UV-induced hydrophilicity [1]. Literature studies show that several techniques for titanium dioxide coatings preparation, such as thermal and electrochemical oxidation (in case of titanium substrates) [2,3], magnetron sputtering [4,5], chemical vapor deposition [6][7][8][9], and sol-gel [2,7,[10][11][12][13] have been investigated. But one of the most frequently used methods is sol-gel due to its high application potential [14].…”
Section: Introductionmentioning
confidence: 99%